A Formal Test of the Origin of Variation in North American Early Paleoindian Projectile Points. Issue 2 (20th April 2009) - Buchanan, Briggs; Hamilton, Marcus J.
Abstract : Recently it has been suggested that variation in the form of Early Paleoindian projectile points across North America was the result of drift rather than regional adaptation (Morrow and Morrow 1999). Here, we test this hypothesis quantitatively with matrix correlation statistics. Using a sample of Early Paleoindian point assemblages from across the continent we attempt to correlate variation in point shape with several measures of late Pleistocene period regional variation including net primary production, prey availability, prey selection, and prey body size. We find no significant correlations between point shape and measures of regional variation, suggesting that functional modifications to points within specific regional biomes were minimal. We do find evidence of spatial autocorrelation as the regional variation in point shape correlates positively with geographic distances among sites, a pattern consistent with recent, shared ancestry. Our findings provide support for the drift hypothesis posed by Morrow and Morrow (1999). We interpret these results as suggesting that despite the wide variation in regional environmental conditions across late Pleistocene period North America not enough time elapsed during the Early Paleoindian period for these local selective gradients to have led to significant changes in point shape.